The emerging role of next-generation sequencing in minimal residual disease assessment in acute lymphoblastic leukemia: a systematic review of current literature - Ștefan, Andreea-Iulia; Radu, Letiția-Elena; Jardan, Dumitru; Coliță, Anca (Frontiers in Medicine, 2025)
BackgroundMinimal residual disease (MRD) is a critical prognostic marker in acute lymphoblastic leukemia (ALL). The well studied and used MRD detection methods, multiparametric flow cytometry (MFC) and real-time quantitative polymerase chain reaction (qRT-PCR) for fusion genes and receptor gene rearrangements have significantly improved risk stratification, but have limitations in sensitivity and applicability. Next-generation sequencing (NGS) has emerged as a promising approach for MRD assessment, offering better sensitivity and the ability to track clonal evolution.ObjectivesThis systematic review evaluates the clinical utility and prognostic value of NGS for MRD detection in ALL, comparing its performance with conventional methods and exploring its potential role in therapeutic guidance.MethodsA comprehensive literature search was conducted across PubMed and Web of Science following PRISMA guidelines. Studies were included if they assessed MRD using NGS in ALL patients and provided data on sensitivity and prognostic value. Comparative analyses with MFC or qRT-PCR were considered. Data on end-of-induction MRD values, event-free survival (EFS), and overall survival (OS) were extracted.ResultsThirteen studies met the inclusion criteria. NGS demonstrated superior sensitivity in detecting MRD-positive cases compared to MFC in patients classified as MRD-negative. Higher correlation was observed in MRD-positive cases than in MRD-negative cases. NGS-based MRD stratification correlated strongly with clinical outcomes, with patients achieving NGS-MRD negativity exhibiting superior EFS and OS rates. Additionally, NGS was highly predictive of relapse following hematopoietic stem cell transplantation and CAR-T cell therapy. The IGH rearrangements as the primary marker in NGS panels has demonstrated good prognostic value in B-ALL.ConclusionNGS represents a transformative tool for MRD monitoring in ALL, offering enhanced sensitivity and prognostic accuracy. Challenges such as high costs, complex bioinformatics analysis and the need for standardization remain. While its integration into clinical practice holds significant promise, further research is needed to establish standardized protocols, cost-effectiveness, and its optimal role in treatment decision-making. The combination of NGS with MFC may provide complementary advantages.